A National Review of State Laws for Stock Epinephrine in Schools. (25th November 2021) - Volerman, Anna; Brindley, Claire; Amerson, Nancy; Pressley, Tiffanie; Woolverton, Nikki
Abstract: Background: Anaphylaxis is a life‐threatening allergic reaction with significant risk for children with allergies. Access to potentially life‐saving medication is critical for these children. This review aims to describe state laws and policies guiding stock epinephrine in schools for allergic or anaphylactic events and detail recommendations for best practices. Methods: This paper is a comprehensive review of the 50 states and the District of Columbia's (DC) laws and policies for stock epinephrine at schools for children in pre‐kindergarten through 12th grade. Results: All 50 states and DC allow undesignated epinephrine in schools to use for allergic or anaphylactic reactions. A key difference arises in whether states allow (N = 37) or mandate (N = 14) that schools stock epinephrine. States exhibit differences in the body responsible for developing stock epinephrine policy (N = 48), along with stakeholders responsible for developing procedures (N = 30) and implementing them (N = 19). Differences also exist in state epinephrine procurement, administration, training, and liability. Conclusions: This review of stock epinephrine laws and policies highlights the significant variation in state legislation despite widespread adoption. Only one‐quarter of states mandate that schools have stock epinephrine available for emergency use, underscoring need for a more unified approach with consistent guidelines, comprehensive training, and possible funding for implementation.